2019
DOI: 10.1002/sd.1930
|View full text |Cite
|
Sign up to set email alerts
|

Does aging‐friendly enhance sustainability? Evidence from Hong Kong

Abstract: The aging population is one of the demographic changes in the 21st century. World Health Organization defines an age‐friendly city as a place that has an “inclusive and accessible urban environment that promotes active aging.” It receives considerable attention in the field of gerontology and contains important aspects of sustainable urban development. Unfortunately, there have not much research that addresses the relationship between aging‐friendly and sustainability. There is a need to modify the market mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…The Ladispoli and Romanian cases are also echoed in a Hong Kong study. Qian et al [45] found that respect, communication and information and community and health services positively associate with environmental sustainability. For activities to promote environmental protection, Clark [46] studied an AFCC project in Philadelphia called GenPhilly.…”
Section: Age-friendly and Sustainable Development-an Integration Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The Ladispoli and Romanian cases are also echoed in a Hong Kong study. Qian et al [45] found that respect, communication and information and community and health services positively associate with environmental sustainability. For activities to promote environmental protection, Clark [46] studied an AFCC project in Philadelphia called GenPhilly.…”
Section: Age-friendly and Sustainable Development-an Integration Perspectivementioning
confidence: 99%
“…The only reference found from Qian et al defines economic sustainability as using existing resources optimally to create continuous economic value and growth. According to their Hong Kong case, social/civic participation and employment and community and health services positively associate with economic sustainability [45].…”
Section: Age-friendly and Sustainable Development-an Integration Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Boyacıoglu [ 3 ] concluded that the population’s age structure is reflected in the dependence burdens and may also affect the ability to save from a given national income. Qian, Ho [ 18 ] studied the aging-friendly and economic, environmental, and social sustainability relationship and found a significant sustainability linkage. Nilsson [ 10 ] posited that sustainable work life is important to all age groups, especially when working life extended to a higher age.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaimuri and Kosimbei [ 17 ] too observed the need for a global paradigm shift to sustainable development to address various problems facing regions and countries. Qian, Ho [ 18 ] lamented the lack of research on the relationship between age structuring and sustainable development. Grazuleviciute-Vileniske, Seduikyte [ 11 ] posited that at present, individual welfare becomes sustainable development and a human- centered approach; therefore, population and associated issues such as health expenditure per capita must be viewed from the perspective of sustainable development, based on social, economic, and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%